ANALISIS PENGARUH CAMELS TERHADAP PERTUMBUHAN LABA PADA SEKTOR PERBANKAN SYARIAH DI INDONESIA PERIODE 2010-2013 - B11111090, DASRIEL HAFIZ (Jurnal Manajemen Update, 2015)
The objectives of this research to fine effects the health of Islamic Banking with using CAMELS method on Earning Growth on 2010 until 2013. Financial ratios are used consisting of KPMM, KAP, NOM, STM, and MR. The data used in this study were obtained from the Financial Statements of Islamic Banks in 2010 to 2013, published by each Bank concerned. After passing through the stage purposive sample, the sample is feasible to use as many as seven samples, 3 Foreign Islamic Banks (Bank Syariah Mandiri, Bank Muamalat Indonesia dan Bank Mega Syariah), and 4 Non-Foreign Islamic Banks (BCA Syariah, Bank Panin Syariah, Bank Rakyat Indonesia Syaria and Bank Bukopin Syariah). Analytical techniques used to see CAMELS effect on Earning Growth with multiple regression analysis. The analysis showed that there are KAP and STM have positive affects and not significant with Earning Growth. NOM affected and significantly with Earning Growth, while MR has negative affect and significantly with Earning Growth. Keywords:       KPMM (Minimum Capital Adequacy), KAP (Quality, of Assets Productive), NOM (Net Operating Margin), STM (Short Term Mismetch), MR (Market Risk) and Earning Growth